An updated checklist of the wild bees of Morocco (Hymenoptera: Anthophila) - Sentil, Ahlam; Ghisbain, Guillaume; Wood, Thomas J.; Bogusch, Petr; Dorchin, Achik; Flaminio, Simone; Kasparek, Max; Kuhlmann, Michael; Litman, Jessica; Michez, Denis; Müller, Andreas; Rasmont, Pierre; et al. (Zootaxa, 2026)
Morocco, encompassing both Mediterranean and Saharan regions, is recognized as a biodiversity hotspot, hosting a rich fauna of wild bees. While taxonomic research on Moroccan bees has accelerated in recent years, an update was needed to provide a more complete taxonomic foundation. Here, we present an updated checklist of Moroccan wild bees since the first complete checklist published in 2020. This work summarises and proposes a total of 143 changes to the previous checklist, which correspond to 14.8% of taxa compared to the first checklist: two new genera for the country (Schmiedeknechtia and Aglaoapis), 36 species recently described as new to science, 37 species recently recorded in Morocco, and 16 species newly reported here for the country. We further document 18 published synonymies, 33 taxonomic acts and clarifications, and provide records for 28 species previously lacking precise data. We also exclude 14 species from the previous checklist and 25 names based on published synonymies and taxonomic acts and clarifications. This update brings the total to 1,043 wild bee species belonging to six families and 70 genera, compared to 961 species in the 2020 checklist, with 10% (108 species) currently considered as endemic to Morocco. This first update, resulting from a collaborative effort among experts, strengthens the taxonomic framework required to advance research on wild bee diversity, endemism, and conservation in Morocco.